Prohibition of Civilians Transfer Under International Humanitarian Law and Its Relation to Genocide - Rusman, Rina; Syofyan, Syofirman (Nagari Law Review, 2024)
Forcible transfers or forced displacements due to an international or non-international war often happen and cause suffering to those who become displaced by loss of their homes and livelihoods and survival resources. As an example of the current situation, there are many civilians from Gaza, especially Palestinians, who have had to leave their homes and have to seek shelter. Alarmingly, some of them have fled to refugee camps that have been housing Palestinian refugees since the 1948 and 1967 conflicts with limited conditions. While, it is commonly known that evacuation should only be temporary. This fact invites us to discuss and answer the following questions: 1) How is the rule of international humanitarian law or the law of war regarding the transfer of population and civilians in time of war?; 2) How could the displacement of civil population and civilian in time of war amount to genocide or ethnic cleansing?; and 3) How is the law enforcement against the violations of international humanitarian law on the transfer of civilian population? It is expected that the answers of these questions could be a reference to comment any news of displacement due to armed conflict. To answer these questions, normative research is conducted by literature study for collecting secondary data from international treaties and other sources of international law such as customary international law, court rulings, expert opinions and information or news from the field, including the implementation of international law in Indonesian national legislation. Analysis of data for taking conclusion is carried out qualitatively, and the reporting is made in an explanatory descriptive manner. The results showed that the international humanitarian law system has contained sufficient rules containing certain prohibitions and obligations for parties to the conflict. There are several prohibitions against deportation and forcible transfer of population. There are several obligations to prevent the forcible transfer or forced displacement of population. There are several obligations to strive for the safety and fulfillment of basic needs of civilians in the event of evacuation and to ensure that the displaced civilians can immediately return to their places of origin. In circumstances, acts that cause forcible transfers or forced displaced civilians might be categorized as war crimes, crimes against humanity and/or genocide. Concerning the violations of the international humanitarian law relating the forcible transfer of civilian population due to war, the state is obliged to carry out the law enforcement against the persons involved who are under its jurisdiction. In addition, no State shall be allowed to absolve itself of any liability incurred by itself in respect of breaches referred to the rules discussed